The Path to Integration: Meeting the Special Needs of Refugee Elders in Resettlement - Jeff Chenoweth; Laura Burdick (Refuge, 2001)
Refugee elders in resettlement represent a small but very vulnerable population. Regardless of age, vitality, or employability, elders play a critical role in upholding a family strength and stability through the difficult period of forced migration. Yet, most resettlement countries provide few services to elders beyond those given to the whole family in the forms of housing, income support, and health care. The lack of elder-specific services may be the result of limited resettlement numbers, inadequate resources, or unfamiliarity with elders’ unique needs. This article discusses the many common needs and challenges of refugee elders through a literature review and follows with recommendations for interventions and integration activities. The authors suggest that skillful needs assessment and creative program design can help to restore elders’ dignity and vitality, thereby strengthening the family unit. The article is based on the authors’ experiences as technical assistance advisers to over 130 private and public refugee elder programs in the United States from 1997 to 2000.